Anionic-nonionic twin surfactant, method for preparing the same, and method for treating aqueous layer
Patent Information
- Application Number
- CN202410475411.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-04-19
- Publication Date
- 2026-10-27
- Estimated Expiration
- 2044-04-19
AI Technical Summary
然而,孪连表面活性剂在地下水修复领域的相关研究却较少
[0018]与现有技术相比,本申请的有益效果包括:
Smart Images

Figure CN118373793B_ABST
Abstract
Description
Technical Field
[0001] This application relates to the field of environmental remediation technology, and in particular to an anionic non-twinned surfactant and its preparation method, as well as an aquifer treatment method. Background Technology
[0002] The problem of groundwater contamination by halogenated hydrocarbons is becoming increasingly serious. Tetrachloroethylene (PCE) and chlorobenzene (MCB), as typical halogenated hydrocarbon pollutants, are dense non-aqueous phase liquids (DNAPLs) frequently detected in groundwater. These substances generally have low water solubility, high interfacial tension, and strong biotoxicity. During aquifer migration, DNAPL is trapped in the pores of the medium in a multiphase form, leading to difficulty in desorption, poor mobility, and slow release into groundwater over a long period. Existing groundwater remediation technologies often have long remediation cycles and high costs, and are prone to pollutant concentration tailing in the later stages of remediation, with concentrations rebounding after remediation is stopped, resulting in unsatisfactory remediation effects. Therefore, DNAPL accumulated in aquifers poses a serious environmental risk to groundwater ecological security.
[0003] Surfactant-enhanced extraction technology has proven to be one of the more effective remediation techniques for DNAPL-contaminated aquifers. Surfactants are commonly used remediation materials in this technology, accelerating contaminant dissolution (solubilization) and reducing oil-water interfacial tension by forming micelles above the critical micelle concentration (CMC). Currently, anionic and nonionic surfactants are frequently used for the remediation of contaminated groundwater, but both have certain drawbacks when applied to aquifers. Anionic surfactants have high CMCs, are prone to precipitation in low-temperature groundwater conditions, have poor resistance to ionic interference, are highly biotoxic, and have limited solubilization capabilities for contaminants. While nonionic surfactants have relatively low CMC values, they suffer significant adsorption losses from the medium and readily emulsify with DNAPL, leading to pore blockage and decreased formation permeability.
[0004] In recent years, gemini surfactants have emerged as a new direction in surfactant research. These are a novel type of surfactant formed by linking two conventional single-chain surfactants through connecting groups. Compared to traditional surfactants, they possess superior properties such as higher surface / interfacial activity, lower critical micelle concentration, stronger wettability, and unique rheological properties, showing great promise in fields such as oil and gas extraction, chemical engineering, nanomaterials, biotechnology, and consumer chemicals. However, research on gemini surfactants in groundwater remediation is relatively limited.
[0005] The underground environment is complex, and due to limitations in molecular structure, commonly used surfactants in aquifer remediation are easily affected by low underground temperatures, inorganic salt ions, and media adsorption, resulting in low material utilization and poor remediation effects. Although many types of novel surfactants have been publicly reported, few are highly effective for groundwater remediation. Summary of the Invention
[0006] The purpose of this application is to provide an anionic non-twinned surfactant and its preparation method, as well as an aquifer treatment method, to solve the above-mentioned problems.
[0007] To achieve the above objectives, this application adopts the following technical solution: This application first provides an anionic non-twinned surfactant having the structure shown in Formula I; Formula I; Where m is selected from 6, 8, 10, 12 or 14.
[0008] Preferably, in Formula I, m is 12.
[0009] Formula I; In Formula I, the two long, straight carbon chains act as hydrophobic groups, enabling this anionic non-ferropolymer twinned surfactant to exhibit lower surface activity and stronger solubilization ability, resulting in lower interfacial tension with pollutants. Furthermore, the number of carbon chains can be specifically controlled to meet specific functional requirements. The hydrophilic group consists of two parts: the glucose structure, as a nonionic hydrophilic group, gives this anionic non-ferropolymer twinned surfactant excellent low-temperature resistance and salt resistance, while also possessing good biodegradability and low biotoxicity. The sodium sulfonate group, as an anionic hydrophilic group, improves the poor water solubility of traditional glycoside surfactants and exhibits stronger negative charge and lower adsorption loss compared to traditional nonionic surfactants containing polyoxyethylene chains. The itaconic acid structure acts as a linking group, connecting the two glucose molecules. Itaconic acid is a biomass product that can replace traditional fossil fuels; it is widely available, inexpensive, has a green structure, and does not pose an environmental pollution risk after decomposition.
[0010] This application also provides a method for preparing the anionic non-twinned surfactant as described above, comprising: Alkyl glycosides and itaconic acid were dissolved in N,N dimethylformamide solvent, and a catalyst and polymerization inhibitor were added to carry out a diesterization reaction to obtain an intermediate product. The intermediate product is mixed with a sulfonating agent and subjected to a sulfonation reaction to obtain the anionic non-twinned surfactant.
[0011] Preferably, the molar ratio of the alkyl glycoside to the itaconic acid is (2-2.5):1, for example, it can be 2:1, 2.1:1, 2.2:1, 2.3:1, 2.4:1 or 2.5:1.
[0012] Preferably, the catalyst is p-toluenesulfonic acid; and the polymerization inhibitor is hydroquinone.
[0013] Preferably, the mass of p-toluenesulfonic acid added is 1.0%-2.0% of the mass of itaconic acid, for example, it can be 1.0%, 1.1%, 1.2%, 1.3%, 1.4%, 1.5%, 1.6%, 1.7%, 1.8%, 1.9% or 2.0%; the mass of hydroquinone added is 0.05%-0.15% of the mass of itaconic acid, for example, it can be 0.05%, 0.06%, 0.07%, 0.08%, 0.09%, 0.10%, 0.11%, 0.12%, 0.13%, 0.14% or 0.15%.
[0014] Preferably, the reaction temperature of the diesterization reaction is 100-140℃, for example, 100℃, 110℃, 120℃, 130℃ or 140℃, and the reaction time is 2-3h, for example, 2h, 2.5h or 3h.
[0015] Preferably, the sulfonating agent is anhydrous sodium sulfite, and the molar ratio of the sulfonating agent to the itaconic acid is (1-1.5):1, for example, it can be 1:1, 1.1:1, 1.2:1, 1.3:1, 1.4:1 or 1.5:1.
[0016] Preferably, the sulfonation reaction temperature is 80-100℃, for example, 80℃, 90℃ or 100℃, and the reaction time is 4-7 h, for example, 4h, 5h, 6h or 7h.
[0017] This application also provides a method for treating an aquifer, wherein the aquifer is treated with the aforementioned anionic non-twinned surfactant.
[0018] Compared with the prior art, the beneficial effects of this application include: The anionic-nonionic twinned surfactant of this application combines the multiple advantages of anionic and nonionic surfactants. It has strong surface activity, low surface tension and critical micelle concentration, and the monomer molecules can be arranged more closely at the interface. It is easier to form micelles at low concentrations. It does not precipitate in the low-temperature underground environment, is not affected by the chemical ions of groundwater, has low adsorption loss, has strong solubilization ability for halogenated hydrocarbon pollutants and does not produce emulsification. The risk of secondary pollution to the aquifer after remediation is extremely low.
[0019] The two long, straight carbon chains of this anionic non-ferropolymer twin surfactant act as hydrophobic groups, enabling it to exhibit lower surface activity and stronger solubilizing ability. It also results in lower interfacial tension with contaminants and avoids secondary pollution. The hydrophilic group consists of two parts: the glucose structure, as a nonionic hydrophilic group, gives this anionic non-ferropolymer twin surfactant excellent low-temperature resistance and salt resistance, while also possessing good biodegradability and low biotoxicity. The sodium sulfonate group, as an anionic hydrophilic group, improves the poor water solubility of traditional glycoside surfactants and exhibits stronger negative charge and lower adsorption loss compared to traditional nonionic surfactants containing polyoxyethylene chains. The itaconic acid structure, acting as a linking group, connects the two glucose molecules. Itaconic acid is a biomass product that can replace traditional fossil fuels; it is widely available, inexpensive, has a green structure, and does not pose an environmental pollution risk after decomposition.
[0020] The preparation method of the anionic non-twin surfactant of this application does not generate toxic or harmful waste gas during the synthesis process. The raw materials used are all non-hazardous, widely available, and inexpensive. The synthesis route is simple and the purification method is relatively convenient. A large amount of product can be obtained in a short time, which has great potential for industrial-scale production. Attached Figure Description
[0021] To more clearly illustrate the technical solutions of the embodiments of this application, the accompanying drawings used in the embodiments will be briefly described below. It should be understood that the following drawings only show some embodiments of this application and should not be regarded as a limitation on the scope of this application.
[0022] Figure 1 The infrared spectrum of the anionic non-twinned surfactant of this application; Figure 2 The graph shows the critical micelle concentration and surface tension results of the anionic non-twinned surfactant of this application. Figure 3 The graph shows the low-temperature resistance results of the anionic non-twinned surfactants in this application; Figure 4 The graph shows the results of the anti-ionic interference ability of the anionic non-twinned surfactant of this application; Figure 5 This is a graph showing the adsorption loss results of the anionic non-twinned surfactant of this application on fine sand and medium sand media; Figure 6 The figure shows a comparison of the solubilizing effect of the anionic non-twinned surfactant of this application and existing surfactants on PCE. Figure 7 This figure shows a comparison of the solubilizing effect of the anionic non-twinned surfactant of this application and existing surfactants on MCB. Figure 8This is a comparison of the solubilizing effects of anionic and non-anionic twinned surfactants with different carbon chain lengths on PCE. Figure 9 The figure shows the flushing and repair effect of the anionic non-twinned surfactant of this application on a simulated aquifer. Figure 10 The anionic non-twinned surfactant of this application and IEO 10 Comparison of the solubilizing effect of S-9 on PCE. Detailed Implementation
[0023] As used in this article: "Prepared from" is synonymous with "comprising". The terms "comprising", "including", "having", "containing", or any other variations thereof as used herein are intended to cover non-exclusive inclusion. For example, a composition, step, method, article, or apparatus that includes the listed elements is not necessarily limited to those elements, but may include other elements not expressly listed or elements inherent to such composition, step, method, article, or apparatus.
[0024] The conjunction "composed of..." excludes any unspecified elements, steps, or components. If used in a claim, this phrase makes the claim closed, excluding materials other than those described, except for associated conventional impurities. When the phrase "composed of..." appears in a clause of the body of a claim rather than immediately following it, it limits only the elements described in that clause; other elements are not excluded from the claim as a whole.
[0025] When a quantity, concentration, or other value or parameter is expressed as a range, a preferred range, or a range defined by a series of upper and lower preferred values, this should be understood as specifically disclosing all ranges formed by any pair of any upper or preferred value with any lower or preferred value, regardless of whether the range is disclosed individually. For example, when the range “1–5” is disclosed, the described range should be interpreted as including ranges “1–4”, “1–3”, “1–2”, “1–2 and 4–5”, “1–3 and 5”, etc. When numerical ranges are described herein, unless otherwise stated, the range is intended to include its endpoints and all integers and fractions within that range.
[0026] In these embodiments, unless otherwise specified, the portions and percentages are all by weight.
[0027] "Parts by mass" refers to the basic unit of measurement that expresses the mass ratio of multiple components. One part can represent any unit mass, such as 1g or 2.689g. If we say that component A has "a" parts by mass and component B has "b" parts by mass, it means the ratio of the mass of component A to the mass of component B is a:b. Alternatively, it can mean that the mass of component A is aK and the mass of component B is bK (where K is any number representing a multiplier). It is important to understand that, unlike parts by mass, the sum of the mass parts of all components is not limited to 100 parts.
[0028] "And / or" is used to indicate that one or both of the described situations may occur, for example, A and / or B includes (A and B) and (A or B).
[0029] The implementation schemes of this application will be described in detail below with reference to specific embodiments. However, those skilled in the art will understand that the following embodiments are only for illustrating this application and should not be regarded as limiting the scope of this application. Unless otherwise specified in the embodiments, conventional conditions or conditions recommended by the manufacturer shall apply. Reagents or instruments used without specified manufacturers are all conventional products that can be purchased commercially.
[0030] Example 1 Alkyl glycoside (APG 12) (0.21 mol), itaconic acid (0.1 mol), and N,N-dimethylformamide (50 ml) were added to a three-necked flask equipped with a stirrer and thermometer. Under N2 protection, the mixture was heated to 130°C to dissolve the raw materials. The catalyst, p-toluenesulfonic acid (1.5% of the mass of itaconic acid), and the polymerization inhibitor, hydroquinone (0.1% of the mass of itaconic acid), were added. A water separator and condenser were attached, and the system was kept at a constant temperature. After 3 hours of reaction, the solvent N,N-dimethylformamide was evaporated by rotary evaporation, and the mixture was dried in a vacuum drying oven for 24 hours. The water separator was removed, and the reaction temperature was adjusted to 90°C. A pre-prepared 35% anhydrous sodium sulfite (0.12 mol) aqueous solution was slowly added dropwise to the esterification flask, maintaining a constant temperature throughout the process. The reaction was stopped after 5 hours. The dissolved water was evaporated by rotary evaporation, and the unreacted raw materials were washed off with ethanol several times. The lower layer was separated to obtain a yellow viscous substance, which was then placed in a vacuum drying oven and dried for 24 hours to obtain a pale yellow gelatinous product, namely the anionic-nonionic twin surfactant of Example 1, named SANG 12 (S-Sugar, A-Anionic, N-Nonionic, G-Gemini).
[0031] Example 2 The synthesis schemes for products with other carbon chain lengths (m=6, 8, 10, 14) are the same as in Example 1. Alkyl glycosides (APG 06, APG 08, APG10, or APG 14) (0.21 mol), itaconic acid (0.1 mol), and N,N-dimethylformamide (50 ml) were added to a three-necked flask equipped with a stirrer and thermometer. Under N2 protection, the mixture was heated to 130°C to dissolve the starting materials. Catalyst p-toluenesulfonic acid (1.5% of the mass of itaconic acid) and polymerization inhibitor hydroquinone (0.1% of the mass of itaconic acid) were added. A water separator and condenser were connected, and the system was kept at a constant temperature. After 3 h of reaction, the solvent N,N-dimethylformamide was evaporated by rotary evaporation, and the mixture was dried in a vacuum drying oven for 24 h. The water separator was removed, and the reaction temperature was adjusted to 90°C. A pre-prepared 35% anhydrous sodium sulfite (0.12 mol) aqueous solution was slowly added dropwise to the esterification flask, maintaining a constant temperature throughout the process. The reaction was stopped after 5 hours. The dissolved water was evaporated by rotary evaporation, and the unreacted raw materials were washed off with ethanol several times. The lower layer was separated to obtain a yellow viscous substance, which was then dried in a vacuum drying oven for 24 hours. The products were named SANG 06, SANG 08, SANG 10, and SANG 14, respectively.
[0032] Example 3 A small amount of the product from Example 1 was mixed with potassium bromide, ground, compressed into a tablet, and then subjected to infrared spectroscopy. The test results are as follows: Figure 1 As shown, 3411 cm -1 The peak represents the stretching vibration of the -OH group on the sugar ring, at 2853 cm⁻¹. -1 and 2924 cm -1 The peaks represent the stretching vibrations of -CH3 and -CH2 on long carbon chains, at 1204 cm⁻¹. -1 1032 cm -1 624 cm -1 , and 530 cm -1 There is a vibrational peak caused by -SO3, at 1724 cm⁻¹. -1 The peak represents the stretching vibration of -C=O. These results demonstrate the successful synthesis of the product SANG 12.
[0033] Example 4 A series of aqueous solutions with varying concentrations were prepared from the product SANG 12 of Example 1. The surface tension at different concentrations was measured using a surface tension meter, and curves were plotted. The inflection point is the CMC value of SANG 12. The results are as follows: Figure 2 As shown, the critical micelle concentration of SANG 12 is 0.05 g / L (0.06 mM), and the minimum surface tension is 28.4 mN / m. The low critical micelle concentration and surface tension of SANG 12 indicate that it possesses strong surface activity.
[0034] Example 5 The product SANG 12 from Example 1 was prepared into a 40 g / L aqueous solution and placed in different low-temperature environments (0℃, 5℃, 10℃, 15℃, 20℃) for 24 h each. Figure 3 As shown, the appearance of SANG 12 solution differs from that of traditional anionic surfactants, with no precipitate forming, indicating that SANG 12 has good low-temperature resistance and water solubility, making it suitable for use in underground low-temperature environments.
[0035] Example 6 The products SANG 12 and SDS from Example 1 were prepared into 40 g / L aqueous solutions. 4%, 3.5%, 3%, 2.5%, 2%, 1.5%, 1.0%, and 0.5% (from left to right) NaCl and 4%, 3.5%, 3%, 2.5%, 2%, 1.5%, 1.0%, and 0.5% (from left to right) CaCl2 were added to each sample, respectively. The mixtures were then allowed to stand for 2 hours. Figure 4 As shown, Figure 4 The left side of the image shows the result after adding NaCl, and the right side shows the result after adding CaCl2. The SANG 12 solution did not show obvious precipitation, while the SDS solution showed a significant amount of precipitate. This indicates that SANG 12 can maintain good stability even under high-salt conditions, overcoming the shortcomings of traditional anionic surfactants in terms of poor resistance to ionic interference.
[0036] Example 7 Aqueous solutions of SANG 12, Tween 80, SDS, TX100, SDBS, and Brij 35 at specific concentrations were prepared and added to medium or fine sand at a water-to-soil ratio of 4:1. After shaking on a shaker for 2 hours, the surfactant concentrations in the solution before and after shaking were measured, and the adsorption capacity of the surfactants was calculated. The test results are as follows: Figure 5 As shown, the adsorption losses of SANG 12 on medium sand and fine sand were 0.54 and 0.9 mg / g, respectively, both of which are much lower than those of commonly used surfactants, indicating that SANG 12 is subject to even lower adsorption losses in aquifer media.
[0037] Example 8 SANG 12 aqueous solutions with concentrations of 5 g / L, 10 g / L, 15 g / L, 20 g / L, 25 g / L, 30 g / L, 35 g / L, and 40 g / L were prepared. Simultaneously, aqueous solutions of different single-chain surfactants (SDS, SDBS, TX-100, Brij35, and Tween-80) at corresponding concentrations were prepared. 300 μL of PCE and 400 μL of MCB were added to each solution, and the solutions were incubated in a constant-temperature water bath with shaking for 48 h. The supernatant was then centrifuged, and the PCE concentration in the aqueous phase was analyzed using liquid chromatography. The test results are as follows: Figure 6 and Figure 7 As shown, SANG 12 exhibits the best solubilizing ability for PCE, reaching approximately 12,000 mg / L at 40 g / L, which is more than two orders of magnitude higher than that of clean water. Although SANG 12's solubilizing ability for MCB is slightly lower than that of Tween 80, it did not show the significant emulsification phenomenon with contaminants that Tween 80 does, indicating that SANG 12 is more suitable for aquifer remediation.
[0038] Example 9 Aqueous solutions of SANG 06, SANG08, SANG10, SANG12, and SANG14 with concentrations of 5 g / L, 10 g / L, 15 g / L, 20 g / L, 25 g / L, 30 g / L, 35 g / L, and 40 g / L were prepared respectively. 300 μL of PCE was added to each solution, and the solutions were shaken in a constant temperature water bath for 48 h. The supernatant was then centrifuged, and the PCE concentration in the aqueous phase was analyzed using liquid chromatography. The test results are as follows: Figure 8 As shown, SANG12 has the strongest solubilizing ability for PCE.
[0039] Example 10 The simulated column used was 14 cm long and 2.5 cm wide. A water distribution plate was installed at the inlet, and 2 mL of PCE was injected. The column was placed horizontally, and rinsed with Tween-80 and SANG 12 solutions at concentrations of 40 g / L, respectively. The test results are as follows: Figure 9 As shown, during the SANG 12 solution flushing process, the highest PCE effluent concentration was observed at 2 PV, reaching 12374 mg / L. After 5 PV flushing, the PCE effluent concentration decreased significantly and approached 0 mg / L, indicating that the PCE removal process was essentially complete at this point. However, during the Tween 80 solution flushing process, the PCE effluent concentration remained consistently low and persisted for a longer period, showing no significant decreasing trend after 10 PV flushing. The highest PCE effluent concentration in the SANG 12 solution was approximately three times that in the Tween 80 solution, indicating that SANG 12 has a higher PCE removal efficiency compared to Tween 80.
[0040] Example 11 The product SANG 12 from Example 1 was compared with the surfactant IEO disclosed in the applicant's prior patent application, CN 15197106 A. 10 Compared to S-9, IEO 10 The hydrophobic groups in the S-9 structure are benzene rings and long carbon chains, while the nonionic hydrophilic groups are polyoxyethylene chains.
[0041] IEO 10 The CMC and surface tension of S-9 are 0.1 mM and 32.3 mN / m, respectively, while those of SANG 12 are 0.06 mM and 28.4 mN / m, respectively. Therefore, SANG 12 has a lower critical micelle concentration and surface tension.
[0042] 40 g / L of SANG 12 and IEO 10 S-9 was treated with 300 μL of PCE, and after shaking in a constant temperature water bath for 48 h, the supernatant was collected and centrifuged. The concentration of PCE in the aqueous phase was analyzed by liquid chromatography. The results are as follows: Figure 10 As shown, SANG 12 and IEO 10 S-9 has a solubilizing capacity of 12312 mg / L for PCE and 8863 mg / L for PCE, while SANG 12 has a stronger solubilizing capacity for PCE.
[0043] Furthermore, the SANG in this application uses a glucose structure as the key functional group and does not contain a benzene ring structure, compared to IEO. 10 S-9 is more biodegradable, green and low in toxicity, and poses a lower risk of secondary pollution after the material is used to remediate polluted aquifers.
[0044] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of this application, and are not intended to limit them. Although this application has been described in detail with reference to the foregoing embodiments, those skilled in the art should understand that modifications can still be made to the technical solutions described in the foregoing embodiments, or equivalent substitutions can be made to some or all of the technical features therein. Such modifications or substitutions do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of this application.
[0045] Furthermore, those skilled in the art will understand that although some embodiments herein include certain features included in other embodiments but not others, combinations of features from different embodiments are intended to be within the scope of this application and form different embodiments. For example, in the foregoing claims, any of the claimed embodiments can be used in any combination. The information disclosed in this background section is intended only to enhance the understanding of the general background of this application and should not be construed as an admission or in any way implying that such information constitutes prior art known to those skilled in the art.
Claims
1. A non-anionic twinned surfactant, characterized in that, The method for preparing the anionic non-twinned surfactant includes: Alkyl glycosides and itaconic acid were dissolved in N,N dimethylformamide solvent, and a catalyst and polymerization inhibitor were added to carry out a diesterization reaction to obtain an intermediate product. The intermediate product is mixed with a sulfonating agent and subjected to a sulfonation reaction to obtain the anionic non-twinned surfactant. The alkyl glycoside is selected from one of APG08, APG10, APG12 and APG14; The molar ratio of the alkyl glycoside to the itaconic acid is (2-2.5):1; The catalyst is p-toluenesulfonic acid; the polymerization inhibitor is hydroquinone; The sulfonating agent is anhydrous sodium sulfite.
2. The anionic non-twinned surfactant according to claim 1, characterized in that, The mass of p-toluenesulfonic acid added is 1.0%-2.0% of the mass of itaconic acid; the mass of hydroquinone added is 0.05%-0.15% of the mass of itaconic acid.
3. The anionic non-twinned surfactant according to claim 1, characterized in that, The diesterization reaction is carried out at a temperature of 100-140℃ for 2-3 hours.
4. The anionic non-twinned surfactant according to claim 1, characterized in that, The molar ratio of the sulfonating agent to the itaconic acid is (1-1.5):
1.
5. The anionic non-twinned surfactant according to claim 1, characterized in that, The sulfonation reaction is carried out at a temperature of 80-100℃ for 4-7 hours.
6. A method for treating aquifers, characterized in that, The aquifer is treated with an anionic non-twinned surfactant according to any one of claims 1-5.
Citation Information
Patent Citations
Anion-non-type twin surfactant, preparation method thereof and application of anion-non-type twin surfactant in repairing halohydrocarbon polluted aquifer
CN115197106A